Farmers’ willingness to pay for Livestock Extension Services - S. Ravi Kumar; K.V.R.Reddy; B. Sudhakar Rao (Journal of Agricultural Extension Management, 2025)
Livestock extension services in India have been traditionally funded, managed and delivered by public sector with significant subsidies or free of cost. But, in the recent past, the quality of these services has deteriorated considerably mainly because of the fiscal deficits faced by Government in their provision. So, taking positive outcomes of experiences of some developing countries like Mali, Cameroun, Chad, Malaysia, Northern Malawi etc. into account (Anteneh, 1984; Mariam, 1993; Angniman, 1996; Babjee, 1996; and Huttner, 2000), cost recovery has been considered as one of the options to enhance the quality of the services, apart from reducing the financial and administrative burden on the Government. As a result, some of the State Animal Husbandry departments, State Agricultural Universities and cooperatives have now started charging for the livestock extension services. Since, major portion of livestock in our country is owned by small, marginal farmers and landless laborers whose ability to pay for the livestock services is poor, hence it is necessary to safeguard their interests while implementing cost recovery measures for livestock extension services. Hence, to provide empirical evidence in this regard, the present study was conducted to study the willingness of the farmers to pay for livestock extension services